Using community‐based participatory methods to design a digital intervention for mothers with substance use disorders: Qualitative results from focus group discussions. Issue 2 (3rd May 2021) - Raynor, Phyllis; Corbett, Cynthia; Prinz, Ron; West, Delia; Litwin, Alain
Abstract: Purpose: This community‐based participatory research project explored the feasibility of delivering parenting and recovery supports through digital technology for mothers recovering from addictive substances. Design and Methods: A community advisory board of key stakeholders ( n  = 7) served as a focus group of advisors to discuss needed supports. Data were analyzed through qualitative descriptive analysis. Findings: Results revealed themes about challenges and supports needed, and whether supports delivered through digital technology may improve recovery and parenting. Practice Implications: Future exploration needs to examine the extent to which the use of community‐guided, tailored digital support applications that supplement prescribed treatment can enhance parenting and recovery.